2015
DOI: 10.1007/s13277-015-4170-z
|View full text |Cite
|
Sign up to set email alerts
|

Alpha-linolenic acid regulates Cox2/VEGF/MAP kinase pathway and decreases the expression of HPV oncoproteins E6/E7 through restoration of p53 and Rb expression in human cervical cancer cell lines

Abstract: Cervical cancer represents the largest cause of mortality in women worldwide. In our previous report, we have shown how alpha-linolenic acid (ALA), an omega-3 fatty acid, regulated the growth of cervical cancer cells. The present study aimed to explore mechanistic details for the anticancer activity of ALA in cervical cancer cell lines, SiHa and HeLa. ALA significantly modulated the growth kinetics of the cells and reduced cell migration with concomitant decrease in the expression of VEGF, MMP-2, and MMP-9 pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 48 publications
2
28
0
Order By: Relevance
“…Therefore, it may be hypothesized that COX-2 has potential as a prognostic biomarker for breast cancer. Previous studies have reported that COX-2 was upregulated and associated with tumor invasiveness and clinical outcome in numerous types of human cancer (27)(28)(29)(30). In the present study, a correlation was revealed between high COX-2 expression and poor differentiation status (P<0.05).…”
Section: Discussionsupporting
confidence: 69%
“…Therefore, it may be hypothesized that COX-2 has potential as a prognostic biomarker for breast cancer. Previous studies have reported that COX-2 was upregulated and associated with tumor invasiveness and clinical outcome in numerous types of human cancer (27)(28)(29)(30). In the present study, a correlation was revealed between high COX-2 expression and poor differentiation status (P<0.05).…”
Section: Discussionsupporting
confidence: 69%
“…The oncoproteins E6 and E7 of hrHPV, especially in HPV16/18, have been proved to play critical roles in cervical cancer through different pathways, including inactivating the products of tumor suppressor genes p53 and Rb, respectively (39,40). RASSf1A can induce cell cycle arrest by engaging the Rb family cell cycle checkpoint and the RASSF1A-induced cell cycle arrest can be relieved by the downstream activators of the G1/S-phase transition (cyclin A and E7) (13,24,41), revealing that E6, E7 may participate in the pathogenetic mechanisms of RASSF1A.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that COX2 is upregulated in different cancers and its elevation results in a poor prognosis such as axillary node and bone metastases, and chemotherapy resistance [ 22 26 ]. Inhibition of COX2 can act in a concerted way with improved therapeutic potential in invasive breast cancer, non small cell lung cancer, bladder cancer and cervical cancer [ 18 , 27 29 ].…”
Section: Introductionmentioning
confidence: 99%